Performance Appraisal Of Zoxamide In Combination With Cymoxanil And Mancozeb In Combating The Blight Diseases Of Tomato (Applied Biological Research, 2017)
Early and late blight are the two major biological constraints that hamper the  yield and quality of tomato. Twelve different treatments, comprising of solo  and combination doses of zoxamide with cymoxanil and mancozeb were  evaluated against these diseases for two consecutive rabi seasons. The pooled  data revealed that in these two seasons, the combination of zoxamide 33% +  cymoxanil 33% WP at the dose of 600 g ha-1 gave best control of both early  and late blight diseases as compared to untreated check, manifesting 68.7 and  77.5% control, respectively. Similarly, the combination of zoxamide 8.3% +  mancozeb 66.7% WP @ 2500 g ha-1 gave best control of both the diseases as  compared to untreated check manifesting a control of 62.5 and 65.3%, respectively. None of the doses of zoxamide 8.3% + mancozeb 66.7% WP and  zoxamide 33% + cymoxanil 33% WP was phytotoxic to tomato plants.
Keywords: Blight disease; resistance; synergistic effect; tomato; zoxamide